Optimization of the classical oral cancerization protocol in hamster to study oral cancer therapy - Santa Cruz, Iara Sofía; Santa Cruz, Iara Sofía; Garabalino, Marcela Alejandra; Garabalino, Marcela Alejandra; Trivillin, Verónica Andrea; Trivillin, Verónica Andrea; Itoiz, María Elina; Itoiz, María Elina; Pozzi, Emiliano César Cayetano; Pozzi, Emiliano César Cayetano; Thorp, Silvia Inés; Thorp, Silvia Inés; et al. (Wiley Blackwell Publishing, Inc, 2020)
Fil: Santa Cruz, Iara Sofía. Comisión Nacional de Energía Atómica; Argentina